P172 Histological healing is associated with decreased clinical relapse in patients with ileal Crohn's disease. (16th January 2018) - Christensen, B; Erlich, J; Gibson, P; Rubin, D T
Abstract: Background: Mucosal healing has emerged as a goal of maintenance therapy in patients with Crohn's disease and is associated with improved clinical outcomes. The role of histological healing is less well defined. This study examines if histological healing is associated with improved clinical outcomes in patients with Crohn's disease confined to the terminal ileum. Methods: Patients with confirmed Crohn's disease isolated to the ileum who had a colonoscopy between September 2005 and June 2015 with biopsies taken from the colon and ileum were identified. Those in clinical remission at the time of colonoscopy were included. Demographic and clinical data were collected from case records. The ileum was evaluated for endoscopic mucosal healing (no ulceration) and histological healing (no active inflammation with no erosions, ulceration or neutrophil infiltration). The primary outcome was clinical relapse defined by an HBI > 4, medication escalation or hospitalisation secondary to disease activity. Clinical relapse-free survival was compared between patients with and without histological and mucosal healing. Predictors of clinical relapse-free survival were determined using Kaplan–Meier analysis, log-rank test and Cox proportional hazard model. Results: Of 101 patients, 22 were diagnosed at <16 years old, 23 (23%) patients had an inflammatory Crohn's disease phenotype (Montreal classification B1), 52 (52%) had penetrating disease (B2) and 25 (25%) stricturing disease (B3). At colonoscopy, 65 (64%) patients had mucosal healing of the terminal ileum and 56 (55%) patients had histological healing on biopsy. The level of agreement between mucosal and histologic activity was fair (agreement for 63% of samples, K = 0.2437, p = 0.0064). 46 (46%) patients experienced clinical relapse with 17 patients requiring hospitalisation and 6 patients requiring surgical intervention at median time of 1.7 years (range 0.003–7.392). On univariate analysis, histological healing ( p = 0.0166) was associated with decreased rates of clinical relapse. Mucosal healing ( p = 0.0735) trended toward a decreased risk of clinical relapse. No other disease- or medication-related characteristics were significantly associated with clinical relapse. On multivariate analysis, only failure of histological healing was associated with risk of clinical relapse (HR 1.85 (95% CI: 1.00–3.44), p = 0.050). Conclusions: In patients with ileal Crohn's disease in clinical remission, histological healing is associated with a decreased risk of clinical relapse and is more predictive than endoscopic mucosal healing. We describe a level of "deeper remission" with associated superior clinical outcomes.